A Glimpse into the Minds of Mothers: The Default Mode Network and Responsiveness to Infant Cries. (3rd April 2019) - Zeifman, Debra M.; Baird, Abigail A.
SYNOPSIS: The authors comment on a paper reporting differences between mothers and non-mothers in neural responses to infant cries and other emotive sounds while engaging in self- or goal-oriented tasks. The value of examining deactivation of the default mode network (DMN) as a means of understanding differential attention patterns in both typical and atypical populations is discussed, as is the generalizability of the experimental paradigm to ecologically relevant contexts. The role of an individual's age, parental status, and experience in shaping responses to infant crying is considered, and future avenues of research are suggested. An argument is made for coupling neuroimaging techniques with behavioral assays to better understand the determinants of maternal behavior.